A Graduate Capability Framework for Environmental Engineering Degree Programs : A Guide for Australian Universities. - Dowling, David; Hadgraft, Roger (Office for Learning and Teaching, 2013)
Guide produced as part of the Define Your Discipline (DYD) Project, which aimed to facilitate curriculum renewal in undergraduate programs. The guide is designed to inform environmental engineering stakeholders about the profession's expectations regarding the capabilities of graduates during their first two or three years of practice. It is expected that each group of stakeholders - Environmental College members; engineering schools, environmental engineering students and employers - will use the guide in different ways.